Practitioner Note 2: Inclusive transfer value, type and payment modalities - Maya Hammad (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Practitioners' Note is the second in a four-part series providing governments in the Middle East and North Africa (MENA) region and practitioners in the fields of social protection and disaster risk management (DRM) with general guidelines for future shock response informed by lessons learned from the COVID pandemic. It provides four best practices of MENA countries in payment types, values and delivery modalities. It also presents immediate and long-term recommendations for enhancing the inclusiveness of those best practices, along with illustrative country cases.
Keywords: 330; disaster risk management; COVID-19; social protection; MENA